Development of a Road Infrastructure Index Model Integrating Disaster Parameters: A Case Study of Solok Regency - Rifki Muchni; P Purnawan; Elsa Eka Putri (Universitas Islam Sultan Agung, 2026)
The road network is a crucial infrastructure that supports mobility and economic activity in a region. In Solok Regency, various issues related to the quality and equity of road network services remain a major challenge, primarily due to the lack of road performance evaluation that considers efficiency, effectiveness, and the impact of natural disasters. This study aims to develop a Road Infrastructure Index (RII) integrated with disaster parameters and predict future RII values. The research method used is a quantitative approach with primary data collection through questionnaires and interviews with stakeholders in the road infrastructure sector, as well as secondary data from relevant agencies. Reliability and validity tests were conducted to verify the consistency and accuracy of the questionnaire. Regression analysis was conducted to determine the model constants. The results of the study obtained a model that can be used to calculate and predict the value of the Road Infrastructure Index. Based on the predicted RII value results in Solok Regency, it was found that the RII value in the coming year will experience a decline.